Pengaruh Kerjasama Tim terhadap Kinerja Pegawai di Akademi Maritim Cirebon - Fereddy Siagian (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study is to find out and analyze studies on the effect of teamwork on employee performance. This research is a quantitative descriptive study with a total sample of 51 respondents, while the sampling technique uses probability sampling method using simple random sampling technique. The results showed that the teamwork variable was obtained by t count (13,170)> t table (2,011). Then the teamwork variable partially influences the employee performance variable, with a sig value of 0,000 <from the value of 0.05. With the value of R Square obtained results of 0.783, this means that teamwork variables influence the change in Y of 0.783 or in other words the effect of the independent variables on the dependent variable is 78.3% while the remaining 21.7% is caused by other variables not included researched within a research framework. Conclusion, the value of the Multiple Correlation Coefficient (R) obtained a value of 0.885 shows that there is a very strong joint relationship between the independent variables of Team Cooperation to the dependent variable, namely Employee Performance. Keywords: Team Cooperation, Employee Performance